Comparative transcriptomics analyses of chemosensory genes of antenna in male red swamp crayfish Procambarus clarkii - Zhou, Zihao; Mo, Lili; Li, Dinghong; Zeng, Wenlong; Wu, Hongying; Wu, Zhengjun; Huang, Jinlong (Frontiers in Ecology and Evolution, 2022)
The red swamp crayfish, Procambarus clarkii, is globally an invasive species and has caused huge damage to aquaculture, biodiversity, and ecology worldwide. Antenna-expressed receptors are important for P. clarkii to detect chemosensory cues for mate attraction. In the present study, we tested the behavior of male P. clarkii to the conditioned water from female P. clarkii during the mating and non-mating periods, and performed RNA sequencing to investigate the chemosensory-related genes of the antenna of male P. clarkii. The results of the behavioral assay have shown that for the same stimulus, male P. clarkii within the mating period can be significantly attracted, but not during the non-mating period. This suggested that chemosensory-related genes of the antenna of male P. clarkii may change obviously with mating seasonal variation. Antenna transcriptomics found that a total of 59218 unigenes with an average length of 1056.41 bp, and 4889 differentially expressed unigenes (DEGs), among which 2128 were up-regulated, while 2761 were down-regulated were obtained. A total of 12 up-regulated and 9 down-regulated DEGs were associated with chemical reception, including 4 IRs or iGluRs, 8 G-protein coupled receptors, 5 transient receptor potential channels (TRP channels), 1 sodium-calcium exchanger, 1 isomerase, and 2 uncharacterized proteins (chemosensory proteins-like, CSPs). CSPs were preliminarily classified as pheromone receptors in the antenna of male P. clarkii. Furthermore, the calcium transduction-related pathways may play an important role in the sex pheromone reception of the male P. clarkii’s antenna. The results of quantitative real-time reverse transcriptase PCR (RT-qPCR) showed that the trends of expression of 8 selected unigenes were consistent with RNA-Seq results. Our results provide more comprehensive data for chemical communication mechanisms after P. clarkii enter the mating period and eventually would develop better control strategies in further.